Shear wave velocity estimation of the near-surface sediments of Bangkok and vicinity, Thailand for seismic site characterization - Aomboon Naksawee (Science Faculty of Chiang Mai University, 2020)
Bangkok and vicinity is located in the Lower Central Plain of Thailand in a region characterized by thick Quaternary basin fills. This region contains the largest city of Thailand (Bangkok) with more than 10 million people and has been affected by distant, moderate to large earthquakes. The average shear wave velocity of the top 30 m of the subsurface (Vs30 ) is an important parameter for seismic site characterization as it can affect the level of ground shaking during an earthquake and thus affect the level of potential damages. In this study, the Vs30 is estimated for Bangkok and vicinity using both passive and active of surface waves methods. The Vs30 of the shallow sediments from 206 sites in Bangkok and vicinity varies from 86 m/s to 207 m/s, which are classified as the soil type Class E and Class D; based on the soil type classification of the U.S. National Earthquake Hazards Reduction Program (NEHRP). In general, the southwestern part of the Lower Central Plain in Sumut Prakan and Chachoengsao has lower Vs30 (Vs30 < 120 m/s) compared to that in the western and northern parts of the study area (Vs30 > 160 m/s). Vs30 maps are generated and they can be used for seismic microzonation, land use planning, and development of Bangkok and vicinity, helping to increase the earthquake preparedness of the city in the future.